2018
DOI: 10.1016/j.jped.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

T-lymphocyte-expressing inflammatory cytokines underlie persistence of proteinuria in children with idiopathic nephrotic syndrome

Abstract: Regardless the level of proteinuria, INS patients had increased expression of TNF-α in CD4-lymphocytes and reduced expression of IFN-γ in CD8-lymphocytes. Persistence of proteinuria was associated with higher levels of inflammatory markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Certain studies have shown that the population of CD8+ T and CD4+ T cells is increased in PNS patients [ 31 , 32 ]. A recent research showed that INS patients had increased expression of TNF- α in CD4-lymphocytes and reduced expression of IFN- γ in CD8-lymphocytes [ 33 ]. B lymphocytes are also involved in the pathogenesis of PNS.…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies have shown that the population of CD8+ T and CD4+ T cells is increased in PNS patients [ 31 , 32 ]. A recent research showed that INS patients had increased expression of TNF- α in CD4-lymphocytes and reduced expression of IFN- γ in CD8-lymphocytes [ 33 ]. B lymphocytes are also involved in the pathogenesis of PNS.…”
Section: Discussionmentioning
confidence: 99%
“…The current study supports these premises and showed reduced inflammatory markers (IL-6 and IL-8) in children with NS versus healthy children. Similarly, in their cohort of children with NS, Guimarães et al found low levels of systemic inflammatory markers including circulating B lymphocytes, and NK and NKT cells [20].…”
Section: Discussionmentioning
confidence: 78%
“…found low levels of systemic in ammatory markers including circulating B lymphocytes, NK and NKT cells [18].…”
Section: Discussionmentioning
confidence: 99%